Climate warming effects on photosynthetic responses of tropical stream macroalgae - Boas, Lucas Kortz Vilas [UNESP]; Oliveira, Régis de Campos [UNESP]; Branco, Ciro Cesar Zanini [UNESP] (Schweizerbart, 2022)
The increase in Earth’s global mean temperature due to anthropogenic climate change threatens many ecosystems. Freshwater ecosystems present characteristics that put their biodiversity at an even greater risk. In low-order tropical streams, benthic organisms contribute to a large fraction of the community energy input from primary producers and play a significant role in sustaining autotrophic food webs. Using the chlorophyll fluorescence and dissolved oxygen evolution techniques, we carried out a laboratory experiment to evaluate the effects of projected temperature increases due to global warming of two future scenarios (Representative Concentration Pathway [RCP] 4.5 and RCP 8.5) proposed by the Intergovernmental Panel on Climate Change (IPCC) on the photosynthetic response of lotic macroalgae. We determined control temperatures in both the summer and winter by taking measurements directly in the field, and we calculated experimental scenario temperatures by adding the projected IPCC increases to the seasonal means. Although there were species-specific responses to the simulated scenarios, we noted some trends. In general, the tested Rhodophyta species showed weakened photosynthetic per-formance, particularly in the highest IPCC-predicted scenario (RCP 8.5). In addition, the temperature increase of the IPCC projected scenarios did not produce significant negative effects on the photosynthesis of most Charophyta and Chlorophyta species, revealing a tolerance of these algae to the tested temperature variations. In some cases, most notably Spirogyra sp., there was an increase in the photosynthetic performance. Given the position of these organisms at the base of the food web, our results indicate that fulfillment of the IPCC scenarios could markedly impact tropical lotic environments, especially in shaded low-order streams, where Rhodophyta constitute a highly relevant group of primary producers.
Keywords: Charophyta; chlorophyll fluorescence; Chlorophyta; climate change; IPCC; lotic ecosystem; primary production; Rhodophyta